Enhancing Speed Control of BLDC Motors Using Zeta Converter for Small Electric Vehicles - Hafidh, Muhammad Yusril; Wibawa, Unggul; Nurwati, Tri; E. Wakama, Tamunonengi (Faculty of Engineering, Universitas Brawijaya, 2023)
The movement to reduce emissions can be done by developing renewable energy and electric vehicles derived from renewable fuels. This electric vehicle will use batteries and motors so that BLDC motor was chosen in this study. BLDC motors use electronic commutation so a controller is needed. The controller used is a PI controller assisted by the hysteresis current controller. The output of the hysteresis current controller needs to be converted to a DC voltage using a DC-DC converter. One of the DC-DC converters is a zeta converter which can increase or decrease the voltage so that it can be used when the load voltage varies as will be used in this study. The results showed that the BLDC motor connected to the zeta converter with the controller can be used when the load torque varies. If the applied varying load torque does not exceed the rated torque, the actual speed will return to the reference speed without exceeding a 10% error. On the other hand, the actual speed will return to the reference speed by exceeding the 10% error, if the applied varying load torque exceeds the rated torque.